The Positivism of the Indonesian Ulema Council’s Fatwa on Dui Menre in Bugis Society: The Perspective of the Qur’an - Suarning; Fikri; Muliati; Saidah; Rukiah (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2025)
This study aims to examine the legal positivization of the Indonesian Council of Ulama’s (MUI) Fatwa No. 2 of 2022 and to explore its potential as a foundation for formal regulation. Employing a descriptive qualitative method with a case study approach, data were collected through document analysis, Islamic legal literature, and interviews with MUI figures and local communities. The findings demonstrate that the fatwa reflects Qur’anic principles of justice, public interest (maṣlaḥah), and equality, while simultaneously affirming the legal status of fatwas as normative products with potential for positivization or legalization into valid written regulations, at least in the form of local bylaws (Perda). The fatwa thus functions as a normative bridge connecting Islamic law, customary norms, and state law. The study recommends synergy between MUI, local government, and traditional leaders to advance the transformation of fatwas into contextual and equitable regulations